A comparative study of corrosion of 316L stainless steel in biotic and abiotic sulfide environments. (May 2017) - Chen, Shiqiang; Frank Cheng, Y.; Voordouw, Gerrit
Abstract: Electrochemical corrosion of 316L stainless steel in a biotic sulfate-reducing bacteria (SRB) culturing medium and an abiotic sulfide sterile solution was investigated by biotesting, cyclic voltammetry and surface characterization techniques. It was attempted to determine if the abiotic sulfide solution is capable of reproducing the corrosive environment that is comparable to that in the biotic SRB medium. Results demonstrated that sulfides generated from SRB metabolism result in a heterogeneous iron sulfide film on the steel surface. Corrosion occurs at locations where sulfides accumulate, increasing the surface roughness of the steel. Like those generated in the biotic medium, sulfides formed in the sterile medium can increase the steel corrosion. However, the generated sulfide film is more uniform, compact and stable than that formed in the SRB medium. Moreover, the steel possesses different cyclic voltammetry behavior. The prepared abiotic sulfide solution is not representative of the SRB medium for corrosion studies. Highlights: Measured cyclic voltammograms of stainless steel in SRB culture medium. Visualized the surface film formed on steel in the SRB culture. Compared the iron sulfide films formed in SRB culture and sterile sulfide solution. Mechanisms for steel corrosion in SRB culture and sulfide solution.